PERAN CUSTOMER RELATIONSHIP MANAGEMENT PADA UMKM LOCKY CHICKEN - Hasan, Golan; Mellysa, Mellysa; Jolie, Veren Apriana; Ricaprio, Jeksen (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This research aims to analyze the implementation of Customer Relationship Management (CRM) at UMKM Locky Chicken, a culinary business in Pontianak which has shown significant development since the end of 2023. In the context of the competitive culinary industry, CRM plays a strategic role in increasing customer loyalty and optimizing business operational efficiency. However, limited resources and technological infrastructure are the main challenges in implementing CRM optimally. This research uses a descriptive qualitative approach with data collection methods through online interviews and social media content analysis (@lockyfood.id). The research results revealed that 80% of customer interactions, including orders, complaints and feedback, were carried out via the WhatsApp and Instagram platforms without an integrated recording system. This condition causes around 30% of complaints related to delivery delays not to be handled effectively. As a recommendation, the study suggests utilizing simple CRM tools such as structured spreadsheets or free CRM platforms such as HubSpot to increase customer retention by up to 20%. These findings can be a reference for MSME players in the culinary sector in designing effective CRM strategies at affordable costs.